Adjusting hydrophily and aromaticity strategy for pitch-based hierarchical porous carbon and its application in flexible supercapacitor. (1st March 2022) - Yang, Yikai; Zuo, Pingping; Qu, Shijie
Graphical abstract: Activation property of coal tar pitch was successfully modified by introducing hydrophilic functional groups and adjusting aromatic structure. Mechanism of the modification was disclosed by analyzing structure changes of the aromatic compounds before and after H2 O2 and HNO3 modification. In addition, the resultant porous carbon showed excellent electrochemical performance as electrode in three-electrode system and all-solid-state device. Highlights: Activation property of CTP was modified by adjusting hydrophily and aromaticity. Modification mechanism was revealed by analyzing aromatic structure changes. PC-CTP (N, O) exhibited excellent electrochemical performance. Abstract: Coal tar pitch (CTP), residue of coal tar distillation process, is regarded as one promising precursor of porous carbon (PC). However, almost all the polycyclic aromatic hydrocarbons (PAHs) in CTP are hydrophobic, their poor dispersion in aqueous solution and insufficient contact with activating agents restrict the activation effect and cause uneven activation easily. Moreover, these PAHs possess easy polycondensation feature in heat-treatment process, which also obstruct the development of pore structures seriously. In this work, we proposed both introducing hydrophilic functional groups and adjusting aromatic structure strategy to modify its activation property. CTP was modified by H2 O2 (CTP (O)) and HNO3 (CTP (N, O)), respectively. After activation, the modified samples derived porous carbon (PC-CTP (O) and PC-CTP (N, O)) had more developed pore structure, especially for PC-CTP (N, O), which possessed high specific surface area (2087 m 2 /g), hierarchical pore structure and certain N content (3.13 wt%). The mechanism was disclosed by analyzing structure changes of PAHs before and after different modifications. Specific capacitance of PC-CTP (N, O) attained 318.1 F/g at 0.5 A/g in three-electrodes system. Two equal PC-CTP (N, O) electrodes were further assembled into flexible cells using PVA/KOH solid electrolyte, and LED lights were lit for more than 4 min by three cells connected in series.